FAKTOR-FAKTOR YANG MEMPENGARUHI RETURN ON INVESTMENT PADA PERUSAHAAN TAMBANG DI INDONESIA - Budi Asmarawati; Andriono Eko Yuniarto; Rahmawati Hanny Yustrianthe (Universitas Negeri Padang, 2022)
This study aims to determine the effect of the Current Ratio, Debt Ratio, Debt To Equity Ratio, and Total Assets Turnover on Return On Investment in Mining Companies listed on the IDX for the 2016-2020 period. This research is a causative research. The population in this study are mining companies listed on the Indonesia Stock Exchange (IDX) as many as 48 companies. While the sample used in this study were 30 companies, the sample selection used a purpose sampling technique. Analysis of the data used is multiple linear regression analysis. The results show that the Current Ratio, Debt Ratio, Debt to Equity Ratio, and Total Asset Turnover have no significant effect on Return On Investment in mining companies listed on the Indonesia Stock Exchange (IDX). ) period 2016-2020. Keywords: Current Ratio (CR), Debt Ratio (DR), Debt to Equity Ratio (DER), Total Asset Turnover (TATO) and Return On Investment (ROI).